(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
The article discusses current issues: The history of international relations in the Central Asian region and neighboring regions indicates interstate interactions. It should be noted that a large amount of archaeological work has been carried out in Central Asia, and one of the main goals of such research was to determine the level of influence of the culture and ideology of different peoples